REVITALIZATION MODEL OF ETHNIC SETTLEMENT TO PRESERVE CULTURAL HERITAGE AND SUPPORT TOURISM IN SURAKARTA - Sariyatun, - (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2010)
The main aim of this research is to formulate a revitalizing model of ethnic settlement through the effort of preserving cultural heritage and supporting community-based tourism in Surakarta. It is a qualitative research which uses primary and secondary sources. The research data is gathered through in-depth interviews, guided group discussions, field observations, and the close reading method [metode simak]. The data was obtained through the triangulation method. The data is then analyzed by using the interactive analysis technique. The results of the research are as follows: First, the kinds of ethnic settlements which still survive are Baluwarti, Kauman, Laweyan, Pecinan in Balong and Kampung Arab Pasar Kliwon. Second, writings on the variety of ethnic settlements in Surakarta are still limited. Therefore, it is necessary to enhance this community-based ethnic settlement through writings so that the community would be better known and be able to benefit from the existing tourism settlement projects. Third, the final model is formulated, i.e. the final Interpretation-Based and Benefit-Oriented Model which is shortened as IBaBOM. This means that what is being constructed is a revitalizing model based on interpretative writings. The objective is to secure benefits for Surakarta.The elements to formulate this model are the potentials, problems, and stakeholders. The potentials refer to the attractions, accessibilities, amenities, and activities. Problems cover matters related to diversifications, collaborations, human resource, thought patterns, and promotion. Stakeholders comprise of the community, the government, higher learning institutions, private enterprises, non-governmental organizations, and associations or â€œpaguyuban.â€ The benefits are the various outcomes which can be enjoyed by all the stakeholders vis-a-vis the process of the empowerment of ethnic communities and the development of culture based tourism in Surakata.According to the Intepretation-Based and Benefit-Oriented Model or (IBaBOM), both the community and the tourists will have knowledge of the history and culture of the ethnic community. The ethnic community as well as the surrounding communities will derive benefits or profits from the undertaking.